Pengaruh ROA, Growth Opportunity, Life Cycle Terhadap Kebijakan Dividen Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index Periode 2015 – 2019 - Vathya Anindita Anindita Putri; A. Dewantoro Marsono (Sekolah Pascasarjana Perbanas Jakarta, 2021)
The purpose of this study is to analyze the effect of Return on Assets (ROA), Growth Opportunity (GO), Life Cycle (LC), on Dividend Policy (DPR) in companies listed on the Jakarta Islamic Index (JII). The sample used includes 16 companies using the purposive sample method. The data used in this study was obtained from the company's annual report for the 2015-2019 period. The technique used in this study uses the panel data regression method. The results showed that ROA and GO did not have a significant effect on the DPR, but LC had a significant positive effect on the DPR. From the results of the F ROA, GO, and LC tests as a whole have a significant effect on DPR.